Elevated Circulatory Levels of Microparticles Are Associated to Lung Fibrosis and Vasculopathy During Systemic Sclerosis - Leleu, Damien; Levionnois, Emeline; Laurent, Paoline; Lazaro, Estibaliz; Richez, Christophe; Duffau, Pierre; Blanco, Patrick; Sisirak, Vanja; Contin-Bordes, Cecile; Truchetet, Marie-Elise (Frontiers in Immunology, 2020)
Background : Microparticles (MPs) are vesicular structures that derive from multiple cellular sources. MPs play important roles in intercellular communication, regulation of cell signaling or initiation of enzymatic processes. While MPs were characterized in Systemic Sclerosis (SSc) patients, their contribution to SSc pathogenesis remains unknown. Our aim was to investigate the potential role of MPs in SSc pathophysiology and their impact on tissue fibrosis. Methods : Ninety-six SSc patients and 37 sex-matched healthy donors (HD) were enrolled in this study in order to quantify and phenotype their plasmatic MPs by flow cytometry. The ability of MPs purified from SSc patients and HD controls to modulate fibroblast’s extra-cellular matrix genes expression was evaluated in vitro by reverse transcriptase quantitative polymerase chain reaction. Results : SSc patients exhibited a higher concentration of circulatory MPs compared to HD. This difference was exacerbated when we only considered patients that were not treated with methotrexate or targeted disease-modifying antirheumatic drugs. Total circulatory MPs were associated to interstitial lung disease, lung fibrosis and diminished lung functional capacity, but also to vascular involvement such as active digital ulcers. Finally, contrary to HD MPs, MPs from SSc patients stimulated the production of extracellular matrix by fibroblast, demonstrating their profibrotic potential. Conclusions : In this study, we provide evidence for a direct profibrotic role of MPs from SSc patients, underpinned by strong clinical associations in a large cohort of patients.